Integrating behavioural theories to advance cervical cancer prevention: insights from Chinese young women. - Xiao, Xizhu; Zhu, Yi (Health Education Research, 2025)
Cervical cancer remains a major threat to women's health. While the Theory of Planned Behaviour (TPB) has been widely used to predict prevention behaviours, gaps in prior research highlight the need for integrated models that explore underlying mechanisms. This study examines cervical cancer prevention intentions among 1027 Chinese young women, the primary audience for such efforts, using a framework that combines TPB, the Extended Parallel Process Model (EPPM), and Protection Motivation Theory (PMT). Structural equation modelling reveals that affective attitude (β = 0.51) is a stronger predictor of human papillomavirus (HPV) vaccination intention than cognitive attitude (β = 0.43) and perceived behavioural control (β = 0.39). For cervical cancer screening, perceived behavioural control (β = 0.42) surpasses injunctive norms (β = 0.28) and descriptive norms (β = 0.17). Additionally, perceived severity negatively impacts affective attitudes towards vaccination (β = −0.26), and response efficacy shows unexpected negative effects on behavioural intentions (βHPV vaccination = −1.34; βcervical cancer screening = −0.36). These findings underscore the importance of addressing emotional distress, enhancing susceptibility perceptions, and correcting misconceptions about response efficacy in health campaigns. This integrated approach offers critical insights for improving cervical cancer prevention strategies in China.